β-Adrenoceptor agonists enhance 5-hydroxytryptamine-mediated behavioural responses - Cowen, P; Grahame-Smith, D; Green, A; Heal, D (1982)
The β-adrenoceptor agonists, salbutamol, terbutaline and clenbuterol, were investigated for their effect on 5-hydroxytryptamine-mediated (5-HT) hyperactivity. The lipophilic β-adrenoceptor agonist, clenbuterol (5 mg/kg) enhanced the behaviours induced by quipazine (25 mg/kg), including headweaving, forepaw treading and hind-limb abduction and thus increased automated activity recording. Clenbuterol (5 mg/kg) also enhanced the hyperactivity syndrome produced by the 5-HT agonist, 5-methoxy N,N-dimethyltryptamine (2 mg/kg) and the combination of tranylcypromine (10 mg/kg) and L-tryptophan (50 mg/kg). Salbutamol and terbutaline potentiated quipazine-induced hyperactivity only when given at the higher dose of 20 mg/kg. The effect of clenbuterol in enhancing quipazine hyperactivity was blocked by the centrally acting β1-adrenoceptor antagonist, metoprolol (5 mg/kg), but not by the β2-adrenoceptor antagonist, butoxamine (5 mg/kg) of the peripherally acting β1-adrenoceptor antagonist, atenolol (5 mg/kg). Clenbuterol (5 mg/kg) did not enhance the circling responses produced by methamphetamine (0.5 mg/kg) in unilateral nigrostriatal-lesioned rats. The results suggest that β-adrenoceptor agonists in common with some established antidepressant treatments produce enhancement of 5-HT-mediated behavioural responses.